Dwell Time Estimation of Import Containers as an Ordinal Regression Problem - Laidy De Armas Jacomino; Miguel Angel Medina-Pérez; Raúl Monroy; Danilo Valdes-Ramirez; Carlos Morell-Pérez; Rafael Bello (Applied Sciences, 2021)
The optimal stacking of import containers in a terminal reduces the reshuffles during the unloading operations. Knowing the departure date of each container is critical for optimal stacking. However, such a date is rarely known because it depends on various attributes. Therefore, some authors have proposed estimation algorithms using supervised classification. Although supervised classifiers can estimate this dwell time, the variable “dwell time” takes ordered values for this problem, suggesting using ordinal regression algorithms. Thus, we have compared an ordinal regression algorithm (selected from 15) against two supervised classifiers (selected from 30). We have set up two datasets with data collected in a container terminal. We have extracted and evaluated 35 attributes related to the dwell time. Additionally, we have run 21 experiments to evaluate both approaches regarding the mean absolute error modified and the reshuffles. As a result, we have found that the ordinal regression algorithm outperforms the supervised classifiers, reaching the lowest mean absolute error modified in 15 (<semantics>71%</semantics>) and the lowest reshuffles in 14 (<semantics>67%</semantics>) experiments.